Mitigative effect of 6-benzyladenine on photosynthetic capacity and leaf ultrastructure of maize seedlings under waterlogging stress - J. WANG; Y.L. WANG; D.Y. WANG; J.X. HUANG; Y.B. LIU; M. ZHU; F.H. LI (Photosynthetica, 2022)
6-Benzyladenine (6-BA) is an artificial synthetic cytokinin, which plays an important role in regulating plant responses to abiotic stress. This study aimed to investigate the mitigative effect of exogenous 6-BA on photosynthetic capacities and leaf ultrastructure under waterlogging stress using two waxy corn inbred lines. The results showed that waterlogging stress disrupted the photosynthesis of waxy corn seedlings. However, exogenous 6-BA alleviated the inhibition caused by waterlogging stress. Under the waterlogging conditions, 6-BA treatment of plants helped preserve the structural integrity of the chloroplasts and retain higher contents of photosynthetic pigments. It also increased the photosynthetic capacity and promoted the openness of stomatal pores. Moreover, exogenous 6-BA promoted photosynthetic activities and the accumulation of carbohydrates. The results revealed that the detrimental effects of waterlogging stress on maize seedlings can be alleviated by 6-BA via modulating photosynthetic activities.